2008
DOI: 10.1007/s12011-008-8164-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dietary Copper Proteinate on Performance, Selected Biochemical Parameters, Lipid Peroxidation, Liver, and Egg Copper Content in Laying Hens

Abstract: This study was performed to determine the effects of copper proteinate on performance, blood chemistry, lipid peroxidation status, and organs as well as copper deposition in the liver and eggs of laying hens. Seventy-two 30-week-old Bovans laying hens were distributed into four groups with three replicates. Animals were fed basal diet containing at least 17% crude protein and 2,800 kcal/kg metabolizable energy supplemented with either 0, 150, 300, or 450 mg/kg copper as copper proteinate. Supplementation of 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 25 publications
3
26
2
Order By: Relevance
“…In line with previous studies in ducks [17], laying hens [18], and broilers [34], copper treatment increased body weight gain and muscle tissue growth in rabbits. At the same time, copper treatment decreased liver and fat weight, suggesting an altered energy redistribution that favored lipolysis.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In line with previous studies in ducks [17], laying hens [18], and broilers [34], copper treatment increased body weight gain and muscle tissue growth in rabbits. At the same time, copper treatment decreased liver and fat weight, suggesting an altered energy redistribution that favored lipolysis.…”
Section: Discussionsupporting
confidence: 90%
“…Dietary copper deficiency is associated with a variety of metabolic changes, including hypercholesterolemia, increased blood pressure, and glucose intolerance, in ducks [17], laying hens [18], and rodents [19,20]. The effect of copper on lipid metabolism has been disputed in previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings are consistent with the study of Minelli et al (2004), who reported that feeding yogurt to rats resulted in decreases in serum AST and ALT, whereas Yoshioka et al (2003) observed that DSW supplementation decreased serum ALT activity in rabbits receiving a diet containing 1% cholesterol. The effect of DSW could be caused by its microelement components, as evidenced by previous studies showing that in rats and laying hens, dietary supplementation with Zn and Cu, respectively, resulted in a reduction of serum AST and ALT (Kechrid and Bouzerna, 2004;Güçlü et al, 2008). Hokanson and Austin (1996) reported that blood TG level is a risk factor for cardiovascular disease independent of HDL-C level.…”
Section: Ast and Alt Activitiesmentioning
confidence: 99%
“…Birds on the diet supplemented with 200 mg/kg of Fe reached lower ADG in the first phase of 21 d. However, trace mineral treatments with different levels of supplementation of the 4 minerals, which were close to the commercial recommendations for the minerals, did not show any further response in the growth performance of broilers in the current research. Supplementation of trace minerals at several fold the trace mineral levels suggested by the NRC [3] would lead to high levels of mineral excretion into the environment [5,7]. With the application of poultry manure, these elements have accumulated in the soil in some regions, and crop yields have been reduced because of high Cu or Zn levels [6,7].…”
Section: Growth Performancementioning
confidence: 99%